2009
DOI: 10.1007/s10565-009-9133-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modification of a baculovirus vector for increased expression in insect cells

Abstract: Generating large amounts of recombinant protein in transgenic animals is often challenging and has a number of drawbacks compared to cell culture systems. The baculovirus expression vector system (BEVS) uses virus-infected insect cells to produce recombinant proteins to high levels, and these are usually processed in a similar way to the native protein. Interestingly, since the development of the BEVS, the virus most often used (Autographa californica multi-nucleopolyhedovirus; AcMNPV) has been little altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 29 publications
0
73
0
Order By: Relevance
“…However, little genetic modification has been performed to increase the amount of foreign products or enhance the activity of the polh promoter in the BEVS. A recent study demonstrated that the deletion of five nonessential genes, v-cath, v-chiA, p26, p10, and p74, from the AcMNPV genome significantly increases the expression levels of recombinant proteins (14). Unlike most AcMNPVbased BEVSs, the BmNPV-based BEVS is particularly suitable for the mass production of foreign proteins in larvae and pupae of B. mori (36).…”
Section: Generation Of Recombinant Bmnpvs Expressing the Fp25kmentioning
confidence: 99%
“…However, little genetic modification has been performed to increase the amount of foreign products or enhance the activity of the polh promoter in the BEVS. A recent study demonstrated that the deletion of five nonessential genes, v-cath, v-chiA, p26, p10, and p74, from the AcMNPV genome significantly increases the expression levels of recombinant proteins (14). Unlike most AcMNPVbased BEVSs, the BmNPV-based BEVS is particularly suitable for the mass production of foreign proteins in larvae and pupae of B. mori (36).…”
Section: Generation Of Recombinant Bmnpvs Expressing the Fp25kmentioning
confidence: 99%
“…This generated virus can be used for primary expression evaluations. After the amplifi cation and titeration of the baculoviral stock, the produced high-titer seed can be used for infection of the insect cells and expression of the recombinant protein of interest in large scale (23,(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, another widely used vector is baculovirus, which has low toxicity and high effi ciency in transgenic gene transfer. Another advantage of this type of vectors is that they do not get integrated into target cell genome [ 25 ]. For example, Lu et al have used baculovirus encoding TGF-β3 to modify MSCs from adipose tissue (ADSCs) to demonstrate that these cells increase chondrogenesis and stimulate cartilage formation in vitro [ 26 ].…”
Section: Viral Nucleic Acid Transfer Techniquesmentioning
confidence: 99%